From Maya to Moksha: Upanishadic Philosophy and Ecological Spirituality in T.S. Eliot’s The Waste Land - Adhikary, Ramesh Prasad (AMC Multidisciplinary Research Journal, 2025)
This study examines T.S. Eliot’s The Waste Land through the lens of Upanishadic philosophy, focusing on its integration of Hindu concepts such as moksha (liberation), maya (illusion), and spiritual renewal to critique spiritual and ecological decay of post-war modernity. Employing a qualitative hermeneutic approach, the analysis combines close readings of the poem and Upanishadic texts with interdisciplinary frameworks from comparative literature and religious studies. Key findings reveal that water imagery functions as a dual symbol of ecological crisis and spiritual awakening, aligning with Upanishadic teachings on Brahman (ultimate reality) and purification. The poem critiques materialism through maya, exposing obsession of modernity with impermanent desires, while ethical imperatives like “Datta, Dayadhvam, Damyata” advocate moral regeneration. Theological tensions between Hindu cyclic rebirth (Samsara) and Christian linear salvation are resolved through the mantra Shantih shantih shantih, which bridges Eastern and Western spirituality. The study concludes that Eliot’s synthesis of Upanishadic metaphysics and modernist poetics offers a universal framework for addressing existential despair, positioning The Waste Land as a cross-cultural dialogue on ethical and spiritual renewal.